Do Refugee Camps Offer a Refuge From Conflict? A Spatially Explicit Analysis of Conflict Incidence at 1,543 Refugee Camps Across Africa (1997–2020) - Fein, Frieda; Van Den Hoek, Jamon (Frontiers in Human Dynamics, 2022)
By the end of 2020, 20.7 million refugees worldwide were under the protection of the United Nations High Commissioner for Refugees (UNHCR). Despite the intended role of refugee camps as sanctuaries for people fleeing conflict and persecution, recent empirical research has shown that many refugees continue to experience conflict even after settling in camps. Measuring refugee exposure to conflict, especially recurrent conflict, is important for the design and evaluation of refugee settlement and asylum policies, refugee-host relationships, as well as refugee security and protection. However, existing research is either nationally aggregated or highly localized at a small number of refugee camps and does not consider changes in conflict incidence following refugee arrivals, leaving uncertainty around near-camp conflict dynamics across refugee hosting countries. To address these gaps, we measured conflict event proximity, frequency, and trends around refugee and non-refugee settlements in all refugee-hosting countries in Africa over a 23-year period (1997-2020). We used georeferenced data on 1,543 refugee camps from UNHCR and conflict event data from the Armed Conflict Location Event Database (ACLED), and compared localized conflict incidence at refugee camps to 4,003 non-refugee settlements from the Global Rural-Urban Mapping Project (GRUMP). Our results show that 52% of all refugee camps and 94% of urban refugee camps were within 10 km of at least one armed conflict event after camp establishment. Conversely, only 82% of urban settlements without refugee camps were within 10 km of a conflict event, suggesting that urban refugee camps are subject to nearby conflict at a disproportionately higher rate compared to both rural refugee camps and non-refugee settlements. We also find that conflict events moved an average of 11.2 km closer to refugee camps after camp establishment, indicating a general encroachment of conflict upon camps. Such persistent and widespread conflict challenges the security of camps and the protections afforded to refugees, and merits increased attention from host countries and humanitarian actors.